2018
DOI: 10.1080/19312458.2018.1483017
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Message Effectiveness Measures in Tobacco Education Campaigns: A Systematic Review

Abstract: Target audience ratings of the likely impact of persuasive messages, known as perceived message effectiveness (PME), are commonly used during message development and selection. PME is also used to examine receptivity of messages after they are fully developed or deployed. Despite this, we know little about the conceptual and methodological characteristics of extant PME measures used in the literature. We conducted a systematic review of tobacco education video, print, and audio campaign studies to examine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 67 publications
1
79
1
1
Order By: Relevance
“…Items (ii) and (iii) were averaged together (α=0.81) into a measure of motivation to behave responsibly and/or not get drunk, and items (iv) and (v) were averaged together (α=0.82) into a measure of motivation to limit drinking around/never supply to minors. Measures of selfreported motivation to engage in behaviour change are often included in measures of perceived message effectiveness, 36 including in a scale that has been validated as a predictor of subsequent intention and behaviour change following exposure to tobacco control ads. 37 After viewing all three ads, participants responded to three questions about their intentions to consume alcohol: In the next week, how likely is it that you will (i) avoid drinking completely, (ii) reduce the number of occasions when you drink alcohol and (iii) reduce the amount of alcohol you have on each drinking occasion.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Items (ii) and (iii) were averaged together (α=0.81) into a measure of motivation to behave responsibly and/or not get drunk, and items (iv) and (v) were averaged together (α=0.82) into a measure of motivation to limit drinking around/never supply to minors. Measures of selfreported motivation to engage in behaviour change are often included in measures of perceived message effectiveness, 36 including in a scale that has been validated as a predictor of subsequent intention and behaviour change following exposure to tobacco control ads. 37 After viewing all three ads, participants responded to three questions about their intentions to consume alcohol: In the next week, how likely is it that you will (i) avoid drinking completely, (ii) reduce the number of occasions when you drink alcohol and (iii) reduce the amount of alcohol you have on each drinking occasion.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A recent systematic review focusing on tobacco education campaigns alone found 75 studies employing 126 PE measures in 21 countries (Noar, Bell et al, 2018). The widespread use of PE is often attributed to its expected utility in message development and selection in the formative phases of persuasive campaigns (Dillard, Weber et al, 2007;Noar, Bell et al, 2018;O'Keefe, 2018a;Yzer et al, 2015). The general idea is that PE would offer a useful indicator of candidate messages' eventual ability to bring about the intended campaign outcomes once they are placed into the market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived message effectiveness (PE) has been widely used in campaign research, both as a tool to assess message potential in formative research (Dillard, Weber et al, 2007;Fishbein et al, 2002), and as a surveillance device to monitor audience receptivity during campaign implementation (Duke et al, 2015;Rath et al, 2019). The last few years have seen a surge of interest in this concept and its application, leading to increased awareness of some important gaps in the literature (Noar, Bell et al, 2018;O'Keefe, 2018aO'Keefe, , 2020Yzer et al, 2015). At the core of the ongoing discussion is the relationship between PE and the attitudinal and behavioral outcomes that campaigns are ultimately interested in (termed actual effectiveness [AE]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, participants have been asked to respond to questionnaire items asking for ratings of messages on persuasiveness, convincingness, effectiveness, and the like (e.g., Mackert et al, 2014;Popova, Neilands, & Ling, 2014), to rank-order messages in terms of persuasiveness (e.g., Mouneyrac, Le Floch, Lemercier, Py, & Roumegue, 2017;Pollard et al, 2016), or to engage in focus-group discussions concerning relative message persuasiveness (e.g., Mowbray, Marcu, Godinho, Michie, & Yardley, 2016;Record, Harrington, Helme, & Savage, 2018). For some general discussions of such measures, see Choi and Cho (2016), Noar, Bell, Kelley, Barker, and Yzer (2018), and Yzer, LoRusso, and Nagler (2015).…”
Section: Message Pretesting and Perceived Persuasiveness Measuresmentioning
confidence: 99%